Previous functional social and behavioral rhythms affect resilience to COVID-19-related stress among old adults - Mauro Giovanni Carta; Michele Fornaro; Luigi Minerba; Massimiliano Pau; Fernanda Velluzzi; Laura Atzori; Cesar Ivan Aviles Gonzalez; Ferdinando Romano; Roberto Littera; Luchino Chessa; Davide Firinu; Stefano Del Giacco; et al. (SAGE Publishing, 2022)
Background: Functioning of Social Behavioral Rhythms (SBRs) may affect resilience toward stressful events across different age groups. However, the impact of SBRs on the coronavirus disease of 2019 (COVID-19) in elder people is yet to ascertain, representing the aim of the present report. Design and methods: Follow-up of a peer-reviewed randomized controlled trial on exercise on old adults (³65 years), concurrent to the onset of the pandemic-related lockdown. Post-RCT evaluations occurred after further 12 and 36 weeks since the beginning of the lockdown phase. People with Major Depressive Episode (MDE) at week-48 (follow-up endpoint) were deemed as cases, people without such condition were considered controls. MDE was ascertained using the Patient Health Questionnaire-9 (PHQ-9); SBRs functioning at week 12 onward, through the Brief Symptom Rating Scale (BSRS). Results: Seventy-nine individuals (53.2%, females) entered the RCT-follow-up phase. The frequency of MDE did not significantly change before versus during lockdown (OR 2.60, CI95%=0.87-9.13). People with BSRS>1 standard deviation of the whole sample score at week-12 had an inflated risk of DE during lockdown (OR=5.6, 95%CI: 1.5-21.4) compared to those with lower BSRS scores. Such odd hold after excluding individuals with MDD at week-12. The post-hoc analysis could be potentially affected by selection bias. Conclusions: Overall, older adults were resilient during the first phase of the pandemic when functioning of pre-lockdown was still preserved, in contrast to the subsequent evaluations when the impairment of daily rhythms was associated with impaired reliance.